Mananjemen Sekuriti di PT Sumber Alfaria Trijaya Tbk. dalam Meningkatkan Keamanan Sistem Data - Edy Soesanto; Achmad ramadhon; Bima Dwi Mardika; Moch. fahmi setiawan (Institut Nalanda, 2023)
Alfamart is one of the largest retail companies in Indonesia engaged in minimarkets.The company was founded in 1989 and has more than 17,000 outlets throughout Indonesia.Given the types of products produced and the large size of the company, data security at PTSumber Alfaria Trijaya Tbk is very important. This research was made to study securitymanagement at PT Sumber Alfaria Trijaya Tbk. in improving the security of data systems. The results show that system security managementat PT Sumber Alfaria Trijaya Tbk is animportant priority to protect sensitive information such as customer data and company finances because PT Sumber Alfaria Trijaya Tbk has a lot of customer information that mustbe keptconfidential toavoid datatheft byunauthorized parties.responsible.